PENERAPAN MODEL PEMBEAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 013 BAGAN HULU - Monaliza '; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Learning science class III SDN 013 Bagan Hulu is low, this is caused by the learning is done by texs oriented book, using the lecture method (conventional) and exercises with student involvement was minimal and many current students passive learning. This study aims to improve student learning outcomes SDN 013 Class III Bagan Hulu through the School Year 2015/2016 "Application of Cooperative Learning Model Two Stay Two Stray (TSTS)". This research was conducted in April 2016. The subjects were 013 third grade students of SDN Bagan Hulu totaling 32 people, consisting of 19 men and 13 women. This study was conducted in two cycles. Instruments of data collection in this study is testing daily tests, observation sheet student activity and teacher activity observation sheet. The average value of the learning outcomes of students has increased where before action 64.81, an increase in UH I to 75.63 and increased again at UH II to 83.38. Improvement of basic scores to the first cycle of 10.82 with peningaktan percentage of 16.68% and an increase of the basic score to the second cycle of 18.57 with a percentage increase of 28.64%. Mastery learning students are also experiencing increasing 43.75% where as before the action is not finished with categories increased 81.25% in the first cycle is not finished with the category increased again in the second cycle 87.50% with a complete category. Activities of teachers and students during the learning process has also increased. Activity Cycle I teachers with an average of 70.83% categorized as good, increased in the second cycle with an average of 89.58% categorized as very good. Activities of students in the first cycle an average of 72.91% with both categories increased in the second cycle average of 87.49% with a very good category. it can be concluded that with the implementation of cooperative learning model Two Stay Two Stray (TSTS) can improve learning outcomes SDN 013 Class III IPA Bagan Hulu. Key Word : Cooperative Type Two Stay Two Stray , Learning Outcomes IPA